Poder y política. El Partido Civil antes de la Guerra con Chile - Mücke, Ulrich (2008)
This article analyzes the rise of the Civil Party before the War with Chile. It studies the outstanding characteristics of the limanian bourgeoisie from which the party arose, as well as the role of the congress, elections and the presidency of Manuel Pardo. Thanks to unified voting patterns the party managed to outweigh the opposition in congress. Elections, which were held every two years, also required a common effort on the part of  the civilists. In spite of its efforts, the party did not carry out any important reform during Pardo’s presidency. Finally, the article explains the elitist social composition of the party and its eminently limanian characteristics.